УСТАЗ ФАХРИДДИН САДИҚОВТЫҢ ӨМИР ЖОЛЫ ҲӘМ ДӨРЕТИЎШИЛИГИ - Жуманиязов, И.Р. (SCIENCE and SOCIETY, 2024)
In the article, the author gives the information about the teachers, the educational process, career, created works, awards of the famous musician, composer Fakhriddin Sadikov on the Chang musical instrument.
Keywords: instruments; the Chang musical instrument; teachers of Fakhriddin Sadikov; educational process; career; created works; awards